FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2014)
This study aims to examine the factors that affect dividend policy perspective with Packing Order and Signaling theory. Factors that affect dividend policy used in this study is free cash flow, profitability, liquidity, leverage, and growth.The selection of the sample in this study using purposive random sampling technique resulted in 46 observation data. This hypothesis was tested using multiple linear regression analysis.The results showed that the free cash flow negative effect on dividend policy. Profitability has a positive effect on dividend policy, liquidity has a posotive effect on dividend policy, leverage negatively effect on dividend policy, and growth has a negative effect on dividend policy.Keywords: Free Cash Flow, Profitability, Liquidity, Leverage, Growth, and Dividend Policy